Leveraging Free Volume Manipulation to Improve the Membrane Separation Performance of Amine‐Functionalized PIM‐1. Issue 12 (12th February 2021) - Mizrahi Rodriguez, Katherine; Lin, Sharon; Wu, Albert X.; Han, Gang; Teesdale, Justin J.; Doherty, Cara M.; Smith, Zachary P.
Abstract: Gas‐separation polymer membranes display a characteristic permeability–selectivity trade‐off that has limited their industrial use. The most comprehensive approach to improving performance is to devise strategies that simultaneously increase fractional free volume, narrow free volume distribution, and enhance sorption selectivity, but generalizable methods for such approaches are exceedingly rare. Here, we present an in situ crosslinking and solid‐state deprotection method to access previously inaccessible sorption and diffusion characteristics in amine‐functionalized polymers of intrinsic microporosity. Free volume element (FVE) size can be increased while preserving a narrow FVE distribution, enabling below‐upper bound polymers to surpass the H2 /N2, H2 /CH4, and O2 /N2 upper bounds and improving CO2 ‐based selectivities by 200 %. This approach can transform polymers into chemical analogues with improved performance, thereby overcoming traditional permeability–selectivity trade‐offs. Abstract : A protection/deprotection strategy was developed to enhance the separation performance of amine‐functionalized PIM‐1. Thermal deprotection yielded a synergistic boost in size‐sieving and CO2 diffusion, ultimately surpassing the H2 /CH4, O2 /N2 and H2 /N2 upper bounds and boosting CO2 permeability by 200 %.